2020
DOI: 10.1186/s12889-020-09597-2
|View full text |Cite
|
Sign up to set email alerts
|

Workforce preparedness for disasters: perceptions of clinical and non-clinical staff at the U.S. Department of Veterans Affairs

Abstract: Background Most U.S. studies on workforce preparedness have a narrow scope, focusing primarily on perceptions of clinical staff in a single hospital and for one type of disaster. In contrast, this study compares the perceptions of workplace disaster preparedness among both clinical and non-clinical staff at all U.S. Department of Veterans Affairs (VA) medical facilities nationwide for three types of disasters (natural, epidemic/pandemic, and manmade). Methods The VA Preparedness Survey used a stratified simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Findings of several studies indicate a direct relationship between a person's actual or perceived level of disaster preparedness According to this study, the chances of attending work among nurses who had previously received trainings pertaining to disasters was higher compared to those who had not, in all three scenarios of earthquake, flood, and epidemic. These findings are consistent with the results of a national survey conducted among pediatric nurse practitioners in the United States (Goodhue et al, 2012) which showed an association between previous training on disasters and the tendency to be present at work following disasters. Past disaster education can have a direct impact on increasing the knowledge and skills needed to manage an emergency situation and a person's actual or perceived competencies (Wu et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Findings of several studies indicate a direct relationship between a person's actual or perceived level of disaster preparedness According to this study, the chances of attending work among nurses who had previously received trainings pertaining to disasters was higher compared to those who had not, in all three scenarios of earthquake, flood, and epidemic. These findings are consistent with the results of a national survey conducted among pediatric nurse practitioners in the United States (Goodhue et al, 2012) which showed an association between previous training on disasters and the tendency to be present at work following disasters. Past disaster education can have a direct impact on increasing the knowledge and skills needed to manage an emergency situation and a person's actual or perceived competencies (Wu et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…The ambiguity of the causes and consequences has a negative effect on a person's preparedness to provide care to the patients, which in turn reduces the desire to attend work (Bell & Wade, 2021). Findings of several studies indicate a direct relationship between a person's actual or perceived level of disaster preparedness and willingness to attend work (Al‐Hunaishi et al, 2019; Choi & Lee, 2021; Dobalian et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 , 32 , 33 Studies have also shown that improving household preparedness will likely increase willingness or ability to report to work or improve level of workforce preparedness during disasters. 8 , 21 , 27 Common barriers to household preparedness often include lack of financial resources, time, and knowledge of how to achieve preparedness. 32 Additionally, personal health problems has been cited as a barrier to ability or willingness to respond during pandemics, 10 , 15 which is particularly poignant during the novel coronavirus outbreak, as pre-existing health conditions has been shown to have a considerable effect on COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For details on the questionnaire and study population refer to previously published work on the VA Preparedness Survey. 21 In accord with the policies regarding activities that constitute human subjects research at the Authors’ Institution, this quality improvement study was determined by the local Institutional Review Board to be a non-research project (#2020-000051), since the study intended to evaluate an existing practice with the intention to improve it based on existing knowledge.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation